Iubeo en César y Salustio: ¿verbo de dos o de tres posiciones? - García de la Calera, Roberto (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
In the present article we intend to demonstrate that iubeo is used by Caesar and Sallust as a two-position verb (milites venire iubet: the accusative milites as the Subject of the infinitive and venire as the Object of iubet) rather than a three-position verb (milites as an Object and venire as a prolative infinitive).